2007
DOI: 10.1007/s10654-007-9187-1
|View full text |Cite
|
Sign up to set email alerts
|

A 5-year comparison of performance of sentinel and mandatory notification surveillance systems for measles in Switzerland

Abstract: A sensitive, specific and timely surveillance is necessary to monitor progress towards measles elimination. We evaluated the performance of sentinel and mandatory-based surveillance systems for measles in Switzerland during a 5-year period by comparing 145 sentinel and 740 mandatory notified cases. The higher proportion of physicians who reported at least one case per year in the sentinel system suggests underreporting in the recently introduced mandatory surveillance for measles. Accordingly, the latter repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…The median time for reporting a suspected measles case was 4 days. This is in agreement with reports from the United States [15], which showed the median time of measles notification to be 4 days (range 1-66 days), and is much better than achieved in Switzerland [16] where a median of 13 days was reported. However, it is still far from the WHO recommendations that at least 80% of suspected cases should be reported within 48 hours.…”
Section: Discussionsupporting
confidence: 92%
“…The median time for reporting a suspected measles case was 4 days. This is in agreement with reports from the United States [15], which showed the median time of measles notification to be 4 days (range 1-66 days), and is much better than achieved in Switzerland [16] where a median of 13 days was reported. However, it is still far from the WHO recommendations that at least 80% of suspected cases should be reported within 48 hours.…”
Section: Discussionsupporting
confidence: 92%
“…In a study done in the US, the passive reporting system identified only 50% of all cases that were identified by the active system in several metropolitan counties in Tennessee [12]. Richard et al [13] showed that the mandatory surveillance system for measles reported 2-to 36-fold lower estimates for incidence rates than the sentinel surveillance in Switzerland.…”
Section: Discussionmentioning
confidence: 99%
“…These systems have higher specificity and better timeliness then mandatory surveillance systems, but they are less sensitive for detecting outbreaks of less common diseases (22). Paediatric sentinel surveillance of vaccine-preventable diseases in Italy showed that the national estimates are 3 to 7 times higher than those obtained through statutory notifications (5).…”
Section: Discussionmentioning
confidence: 99%